Living beyond the limitation: Rehabilitation, life and productivity of individuals with schizophrenia in South‐West Nigeria - Oyeyemi Olajumoke Oyelade; Nokuthula Gloria Nkosi‐Mafutha (Wiley, 2021)
Abstract Introduction Schizophrenia, the most chronic and stigmatized form of mental illness, can be described as a brain disorder that affects an individual's cognition. Individuals with schizophrenia exhibit socially unacceptable symptoms that affect their psychosocial lives. They suffer from reduced productivity due to the debilitating effect of the illness, and the negative symptoms impede their employability; such symptoms and effects aggravate the stigma around mental illness. However, when rehabilitation is successfully achieved, so is productivity, and this decreases the associated stigma. Thus, this study describes the rehabilitation experiences and productivity of individuals with schizophrenia in South‐West Nigeria. Methods and analysis A descriptive qualitative approach with semi‐structured interviews was used to gather information from mental health service users. The discharged users in this study received in‐hospital or outpatient rehabilitation care at four outpatient units within two specialist mental health‐care facilities in South‐West Nigeria. These facilities offer vocational training and rehabilitation services for individuals with schizophrenia. Twenty‐nine mental health service users were interviewed. The data from the interviews were independently analysed by two researchers through a content analysis approach using NVIVO version 11. The researchers compared the results of the analysis and reached an agreement on the conclusion. Findings and recommendations The rehabilitation services availed by patients in the research setting are of three types. Some attend occupational rehabilitation to learn a trade; they depend on professionals for the choice of skill but at a cost that is not affordable to many. Some stay in rehabilitation units linked to the hospital, rendering their services at a cost, and their living expenses and skill acquisition processes are based on the remuneration they get from the services rendered to the institution. Others depend on their family members' efforts to afford rehabilitation services but set up on job by family or employed in family business. The mental health service users in this study who offered their services to the institutions were able to make informed decisions and showed better performance with their chosen occupation than those who depended on their family or health professionals for the choice of rehabilitation service or vocational career. Therefore, this study concludes that prioritizing mental health facility users' preferences in terms of productive activities (sales, services, vocation) or rehabilitation goals should be encouraged.